Industrial Symbiosis: towards a design process for eco-industrial clusters by integrating Circular Economy and Industrial Ecology perspectives. (10th April 2019) - Baldassarre, Brian; Schepers, Micky; Bocken, Nancy; Cuppen, Eefje; Korevaar, Gijsbert; Calabretta, Giulia
Abstract: Industrial Symbiosis (IS) is a collective approach to competitive advantage in which separate industries create a cooperative network to exchange materials, energy, water and/or by-products. By addressing issues related to resource depletion, waste management and pollution, IS plays an important role in the transition towards sustainable development. In the literature, two conceptual perspectives on IS can be identified: the Industrial Ecology (IE) and the Circular Economy (CE) perspective. Despite the recognition of these two perspectives, their relationship remains unclear and explicit attempts to develop an integrated perspective have not been made yet. Consequently, the goal of this research is to highlight and start addressing this critical gap of knowledge in order to support future research and practice geared towards the design of new IS clusters. We pose the following research question: How can the IE and CE perspectives on IS be combined in order to support the design of IS clusters? To this end, we first investigate the two perspectives more in depth and compare them in terms of nature, features and relevance for the study of IS. This is done by applying them as conceptual lenses for the analysis of the same case study, an existing IS cluster. The comparative analysis provides insights into how the two perspectives differ, ultimately demonstrating that they are complimentary and both necessary to fully describe an IS cluster. While the CE perspective is more suitable to explain how a cluster functions from a business standpoint in the operating phase, the IE perspective is more suitable to explain its development over time and its impacts on the environment, the economy and society. Building upon the outcomes of the comparative analysis, we leverage on the discipline of Strategic Design and integrate the two perspectives into a process for designing new IS clusters. We suggest two directions for future research. First, improving our comparative analysis of the two perspectives by looking at a wider sample of IS clusters of different sizes and in different contexts. Second, focusing with more specificity on the issue of how IS clusters can be designed, potentially by trying to apply the process we propose on a real case aimed at designing a new IS cluster. Graphical abstract: Image 1028 Highlights: Industrial Symbiosis is studied from two perspectives: Circular Economy and Industrial Ecology. We analyze the two perspectives and find they are both necessary to define Industrial Symbiosis clusters. We combine these two complimentary perspectives into an integrated process to design new Industrial Symbiosis Clusters.